PENGARUH KUALITAS SDM, UKURAN USAHA DAN LAMA USAHA TERHADAP PEMAHAMAN PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM (Studi Kasus Pada Umkm Di Kota Metro) - Meilinda Andayani; Nedi Hendri; Suyanto Suyanto (Universitas Muhammadiyah Metro, 2021)
This study aims to determine the effect of the quality of human resources, business size and length of business on understanding the preparation of financial statements based on SAK EMKM on MSMEs in Metro City. The research design used in this study is all MSMEs recorded as assisted by the Cooperatives, MSMEs, and Industry Offices in 2019, totaling 101 business fields. The sampling technique that will be used is purposive sampling, so that a sample of 70 respondents is obtained. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the quality of human resources does not have a significant effect, the size of the business has a significant effect, the length of business has an effect on the understanding of the preparation of financial statements based on SAK EMKM.